Mineral Content In Mineral Content In Saliva And Its Saliva And Its Relation To Relation To Ovulation Cycle - Nordin, Norfaizah (2007)
This research is conducted is to prove that potassium concentration is that potassium concentration is the highest during ovulation. the highest during ovulation. To discover discoverthe correlation between the the correlation between the electrolytes concentration in saliva electrolytes concentration in saliva during ovulation. during ovulation.